The role of monogenic genes in idiopathic Parkinson’s disease - Xylena Reed; Sara Bandrés-Ciga; Cornelis Blauwendraat; Mark R. Cookson (Neurobiology of Disease, 2019)
In the past two decades, mutations in multiple genes have been linked to autosomal dominant or recessive forms of monogenic Parkinson’s disease (PD). Collectively, these monogenic (often familial) cases account for less than 5% of all PD, the majority being apparently sporadic cases. More recently, large-scale genome-wide association studies have identified over 40 loci that increase risk of PD. Importantly, there is overlap between monogenic and sporadic PD genes, particularly for the loci that contain the genes SNCA and LRRK2, which are mutated in monogenic dominant PD. There have also been reports of idiopathic PD cases with heterozygous variants in autosomal recessive genes suggesting that these mutations may increase risk of PD. These observations suggest that monogenic and idiopathic PD may have shared pathogenic mechanisms. Here, we focus mainly on the role of monogenic PD genes that represent pleomorphic risk loci for idiopathic PD. We also discuss the functional mechanisms that may play a role in increasing risk of disease in both monogenic and idiopathic forms.